Calcarisporium xylariicola sp. nov. and introduction of Calcarisporiaceae fam. nov. in Hypocreales - Jing Zu Sun (2018)
© 2017, German Mycological Society and Springer-Verlag Berlin Heidelberg. During a survey of fungicolous fungi, a novel taxon from the surface of stroma of an unidentified Xylaria species was collected. Phylogenetic analyses showed that this taxon clustered with Calcarisporium sp. and C. arbuscula isolates, but was resolved as a distinct species. A detailed morphological examination coupled with phylogenetic analysis indicated that the taxon represented a new species. Calcarisporium xylariicola sp. nov. is thus introduced. The new taxon is characterized by short conidiophores with swollen bases and less length/width ratio of conidia that distinguish it from other Calcarisporium species. Calcarisporium is presently placed in Hypocreales genera, incertae sedis genus. Species in the genus are largely fungicolous, or occasionally caulicolous or foliicolous, and have hyaline, erect, verticillate conidiophores and sympodial, polyblastic conidiation. A phylogenetic analysis of combined SSU, ITS, LSU, TEF and RPB2 sequence data from Calcarisporium species and other taxa in Hypocreales indicate that Calcarisporium is a distinct lineage from other families. Therefore, a new family, Calcarisporiaceae, in Hypocreales is introduced.